Trash to treasure: A novel chemical route to synthesis of NiO/C for hydrogen production. (21st June 2019) - Lu, Shun; Hummel, Matthew; Gu, Zhengrong; Gu, Yan; Cen, Zhisheng; Wei, Lin; Zhou, Yue; Zhang, Caizhi; Yang, Chi
Abstract: Transition metal oxides (TMOs), especially nickel oxide (NiO), are environmentally benign and cost-effective materials, and have recently emerged as potential hydrogen evolution reaction (HER) electrocatalysts for future industrial scale water splitting in alkaline environment. However, their applications in HER electrocatalysts remain challenging because of poor electronic conductivity and unsatisfactory activity. Besides, the disposal of eggshell waste is also an environmentally and economically challenging problem as a result of food industry. Here, we report the synthesis of NiO nanoparticles (NPs) encapsulated in the carbonization of eggshell membrane via a green and facile approach for HER application. Noteworthy to mention here that the active carbon was made from the waste, eggshell membrane (ESM), meanwhile, the eggshell was used as a micro-reactor for preparation of electrocatalyst, NiO/C nanocomposite. Then, the as-prepared NiO/C nanocomposite was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) and energy dispersive x-ray spectroscopy (EDS). The SEM, EDS and TEM images reveal that NiO nanoparticles distributed on the carbon support, and XRD patterns confirm the presence of the nanoparticles are NiO and C hybrids. The catalytic activity and durability of NiO/C nanocomposite was examined for HER in 1 M KOH solution. It has been observed that NiO/C nanocomposite showed the better catalytic activity with the smallest Tafel slope of 77.8 mV dec −1 than single component's result, NiO particles (112.6 mV dec −1 ) and carbonization of ESM (94.4 mV dec −1 ). It indicates that the HER performance of electrocatalyst can be enhanced by synergistic effect between NiO particles and carbonization of ESM, with better durability after 500 CV cycles. Furthermore, such design principle for developing interfaces between TMOs and C by a green and facile method can offer a new approach for preparing more efficient electrocatalysts. Highlights: We present a facile and green method to prepare NiO/C nanocomposite for hydrogen production. The waste eggshell and eggshell membrane are regarded as reactor and carbon source, respectively. NiO/C nanocomposite shows better HER performance than the single component.